2013
DOI: 10.1080/01639625.2013.848122
|View full text |Cite
|
Sign up to set email alerts
|

Growin' Grass: Paradise by the Sodium Light

Abstract: This qualitative study describes members of a little-known and little-researched subculture: small-time marijuana cultivators in the United States. Couched within a symbolic interaction theoretical framework, extensive ethnographic interviews were conducted with eighteen marijuana growers who cultivate cannabis plants in their homes for small sales and personal use. This study creates a typology of growers based on motivation for growing and techniques of cultivation. The authors also illustrate how marijuana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…For example, Schensul et al.’s (2000) “The High, the Money, and the Fame” documents user perceptions of the “new” higher potency marijuana strains appearing in the 1990s, and how this contributed to altered gender roles and reputations on the illicit, youth‐oriented street market. Less than a decade later, an ethnography by Chapkis and Webb (2008) documents the increasingly public political struggle to liberalize medical marijuana policy, and by Wiecko and Thompson's (2014) “Growing Grass,” we see a decidedly well‐educated, older, middle class group of “health‐conscious herbalists” growing their own plants for medicinal purposes (337) (see also the excellent ethnography by sociologists Newhart and Dolphin (2019)). Anthropological work on policy documents the unevenness of this transition.…”
Section: The Anthropology Of Drug and Pharmaceutical Usementioning
confidence: 99%
“…For example, Schensul et al.’s (2000) “The High, the Money, and the Fame” documents user perceptions of the “new” higher potency marijuana strains appearing in the 1990s, and how this contributed to altered gender roles and reputations on the illicit, youth‐oriented street market. Less than a decade later, an ethnography by Chapkis and Webb (2008) documents the increasingly public political struggle to liberalize medical marijuana policy, and by Wiecko and Thompson's (2014) “Growing Grass,” we see a decidedly well‐educated, older, middle class group of “health‐conscious herbalists” growing their own plants for medicinal purposes (337) (see also the excellent ethnography by sociologists Newhart and Dolphin (2019)). Anthropological work on policy documents the unevenness of this transition.…”
Section: The Anthropology Of Drug and Pharmaceutical Usementioning
confidence: 99%
“…International studies have shown a connection between the size of the plantation and the level of criminal behaviour of those involved in cultivation. As more cultivation has moved to family settings, less involvement of criminal hierarchies have been noticed (Hakkarainen & Perälä 2011;Wiecko & Thompson 2014;Potter & Klein 2020;Kirby & Peal 2015). However, in the literature, there is a division between cultivation for non-profit purposes and profit purposes.…”
Section: C) Criminal Records Of the Accusedmentioning
confidence: 99%
“…We have also studied the profile of entrepreneurs and growers. Similar typologies have been established using the grower's motivations and the size of plantations as the main criteria (Hough et al, 2003;Potter, 2008;Spapens, 2011;Weisheit, 1992;Wiecko & Thompson, 2014). Non-commercial growers exhibit a wider range of motives.…”
Section: Introductionmentioning
confidence: 95%